(untitled) (The Review of Diabetic Studies, 2025)
Ayurveda explains health and disease through the fundamental principles of Doṣa, Dhātu, Mala, and Agni. The branch of Ayurveda dealing with pathological alterations occurring in these entities is known as Vikṛti Vijñāna. It provides a comprehensive understanding of disease manifestation, progression, diagnosis, prognosis, and treatment. The present article reviews the classical concepts of Śārīrika and Mānāsika Doṣas, Dhātu formation and nourishment, Mala production, Doṣa–Dūṣya interaction, and the clinical importance of Vikṛti Vijñāna. Classical references from Caraka Saṁhitā, Suśruta Saṁhitā, and Aṣṭāṅga Hṛdaya are critically analyzed. Understanding Vikṛti Vijñāna is essential for identifying disease at an early stage, understanding Samprāpti, and selecting appropriate treatment modalities.